(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides information about safety rules in each classroom of the school, the presence of a safety corner where materials with information on water, basic emergency services are placed in case of a fire, electricity to elementary students, everything that it allows us, and interesting ways to teach us about risks.